2019
DOI: 10.1002/aoc.4935
|View full text |Cite|
|
Sign up to set email alerts
|

A novel series of M(II) complexes of 6‐methylpyridine‐2‐carboxylic acid with 4(5)methylimidazole: Synthesis, crystal structures, α‐glucosidase activity, density functional theory calculations and molecular docking

Abstract: Novel complexes of 6‐methylpyridine‐2‐carboxylic acid and 4(5)methylimidazole, namely [Mn(6‐mpa)2(4(5)MeI)2] (1), [Zn(6‐mpa)2(4(5)MeI)2] (2), [Cd(6‐mpa)2(4(5)MeI)2] (3), [Co(6‐mpa)2(4(5)MeI)2] (4), [Ni(6‐mpa)2(4(5)MeI)(OAc)] (5) and [Cu(6‐mpa)2(4(5)MeI)] (6), were synthesized for the first time. The structures of complexes 1–4 and complexes 5 and 6 were determined using X‐ray diffraction and mass spectrometric techniques, respectively. The experimental spectral analyses for these complexes were performed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…Changing metals for the other complexes 1 and 3 – 5 did not have a notable effect on α‐glucosidase inhibition. It can be stated that this difference arises from the fact that the atomic diameter of Hg metal is greater than that of the other Co, Mn and Ni metals. The variation of metals and coordinating ligands for complexes 1 and 3 – 5 did not have an important effect on inhibitory activity results (IC 50 > 600 μM). For complexes 1 and 4 (IC 50 > 600 μM), moving the methyl group from 3‐position to 6‐position at the mpa showed no change on α‐glucosidase inhibition. The IC 50 values of Cu(pa) 2 , Zn(pa) 2 , VO(pa) 2 and Zn(6mpa‐ma) 2 SO 4 complexes have been observed at 1.28 μM, 15.4 μM, >1 mM and 9.6 μM, respectively. In the last few years, it has been observed that the studies with regard to synthetic or natural α‐glucosidase inhibitors have also increased markedly .…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Changing metals for the other complexes 1 and 3 – 5 did not have a notable effect on α‐glucosidase inhibition. It can be stated that this difference arises from the fact that the atomic diameter of Hg metal is greater than that of the other Co, Mn and Ni metals. The variation of metals and coordinating ligands for complexes 1 and 3 – 5 did not have an important effect on inhibitory activity results (IC 50 > 600 μM). For complexes 1 and 4 (IC 50 > 600 μM), moving the methyl group from 3‐position to 6‐position at the mpa showed no change on α‐glucosidase inhibition. The IC 50 values of Cu(pa) 2 , Zn(pa) 2 , VO(pa) 2 and Zn(6mpa‐ma) 2 SO 4 complexes have been observed at 1.28 μM, 15.4 μM, >1 mM and 9.6 μM, respectively. In the last few years, it has been observed that the studies with regard to synthetic or natural α‐glucosidase inhibitors have also increased markedly .…”
Section: Resultsmentioning
confidence: 72%
“…In addition, the effects of some metal complexes containing heterocyclic picolinic acid and its derivatives on diabetes have been investigated . In other work, the IC 50 values of Zn(pa) 2 , Cu(pa) 2 , Zn(6‐mpa–ma) 2 SO 4 and VO(pa) 2 as α‐glucosidase inhibitors have been measured . To date, no other studies reporting α‐glucosidase inhibition activity of mixed‐ligand–metal complexes containing 6‐mpa except for our studies have been performed …”
Section: Introductionmentioning
confidence: 99%
“…Many transition metal complexes of these ligands have been extensively studied because of their great coordination potential and biological importance. [4][5][6][7][8][9][10] Recently, the coordination compounds of bromo derivatives of picH to d-block metals (Co(II), Ni(II), Cu(II), and Ru(II)) have been investigated. [11][12][13][14][15] In these studies, the cobalt(II), nickel(II), copper(II), and ruthenium(II) complexes of 6-bromopicolinic acid (6-BrpicH) were synthesized, and generally, their structural, thermal, spectroscopic, and magnetic properties were examined.…”
Section: Introductionmentioning
confidence: 99%
“…[6,[16][17][18][19][20][21] Furthermore, the metal complexes synthesized with nitrogen-containing ligands have encouraged to research the enzyme activity studies because of their structurally and catalytically similarity with some enzyme-substrate complexes in our body. [7][8][9][10] Due to the ever increasing technological requirements, researching new NLO motifs to meet the needs in these fields is still an important study field. Research of recent NLO materials has focused intensely on metal-organic complex structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation